KEKERASAN RUMAH TANGGA TERHADAP WANITA: KAJIAN PERBANDINGAN SOSIO-PERUNDANGAN DI MALAYSIA DAN INDONESIA - Hanafi Arief; Rohani Abdul Rahim (Al-Adl : Jurnal Hukum, 2015)
In the present era of pursuing a developed country, family life becomes very challenging and this raised pressure on livelihood needs that are not easily predictable. This causes married couples to face many problems including in having mutual understanding, respect and protection. As a result almost every year, there has been an increase of domestic violence (DV) cases, which was conducted by husbands onto wives. Theoretically, DV victims are controlled, suppressed and abused physically, psychologically and economically because of their weaker position, whom are considered inferior compared to the perpetrator that are more superior. The meaning of "domestic violence" depends significantly on whose perspective it is interpreted either they are of the perpetrators, the victims or the law enforcers. Therefore, this writing conducts an in-depth study to understand the meaning of DV, that causes, forms, and effects legal implications and its enforcement in Malaysia and Indonesia.Internally, the roots of violence are associated with victims’ attitude that challenge the offenders, less appreciative towards husband, dependence, adhere to the perpetrator (do not want to report) and strictly adhere to traditions and customs. Externally, DV can be initiated from the perpetrator’s personality, life pressure, gender biases  and social perceptions, financial management weaknesses, paternalistic culture and the misunderstood culture. Effects of DV can be physical hurt, psychological, and econmical effects on family members. Violence Against Women (VAW) resulted in the establishment of The Declaration of the Elimination of Violence Against Women United Nations, 1993, that intends to protect women from discrimination and domination due to powers practiced arbitrarily by male perpetrator.  In Malaysia, the Domestic Violence Act 1994 (Act 521) and in Indonesia, the Republic of Indonesia Law No. 23 of 2004 on the Elimination of Domestic Violence (EDV) provide specific legislation to protect victims. Key Words: Domestic Violence Againts Women, Comparative Socio-legal Research